Konstruksi Tafsir Akademik di Perguruan Tinggi Keagamaan Islam Negeri - Faizin (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2018)
This article discusses the development of writing academic interpretations at PTKIN, specifically the interpretation dissertation written at the Postgraduate School of Syarif Hidayatullah UIN and Sunan Kalijaga UIN Postgraduate Program, using the sociology of knowledge approach. The results of this study indicate that the development of academic interpretations at PTKIN shows a significant increase in symptoms along with the changing social order of contemporary society with all forms of complexity and following the dynamics of the development of contemporary science, both in the East and in the West. Regarding social reality, academic interpretation seeks to find solutions to various social problems that occur in the community. This generally shows a shift in the paradigm of interpretation from normative to emancipatory. Regarding the reality of the development of contemporary science, academic interpretation seems responsive and dialectical. This shows an attitude of openness to the dynamics of the development of contemporary science. Overall, it can be concluded that the academic interpretation in PTKIN no longer revolves around the theocentric-ideological or ideological-opportunistic reasoning area, but has shifted to the anthropocentric-dialectical region.